ANALISIS TATA LETAK ALAT PRODUKSI BUKU TAHUNAN MENGGUNAKAN SYSTEMATIC LAYOUT PLANNING (SLP) DAN BLOCPLAN (STUDI KASUS: CV RENJANA OFFSET) - Wisnu Alfian Majid; Andung Jati Nugroho (CV. ALIM'SPUBLISHING, 2023)
A good facility layout will affect the smooth production process. Preliminary observations on CV Renjana Offset are still not good enough to apply because they do not take into account the degree of closeness. This can be seen from the location of the machine and work stations that look far apart and the existence of intersecting material flows resulting in backtracking, such as the printing work station to the coating work station, the material transfer distance is 12.4 m and has to pass through the garden and back of the CV Renjana Offset office with distances that are too long cause the production time to be longer. The method used to design the layout of production facilities at CV Renjana Offset is the Systematic Layout Planning and Blocplan methods. This method was chosen because it is in accordance with the characteristics of the company and can minimize the distance between production stations and no longer intersecting production process flows. This research was conducted with the aim of knowing and getting an increase in the efficiency of the initial material handling layout with layout suggestions. The results of the calculation of the total area needed for assistance are 171.5 m². The results of SLP and Blocplan processing are 10 alternative layouts and the Adjacency score, R Score, and Rel-dist score feature values ​​are presented for each layout alternative. Of the 5 alternative layouts produced, there is a layout for the production of yearbook products which is chosen as the best layout because it has an Adjacency Score of 1.00, layout 2 has an R Score of 0.87, and the Rel-dist Score of the second layout has a value of 202. Based on three parameters, The selected layout is layout 2. Calculation of distances using the rectilinear method at each facility for the yearbook product layout is 28.29 m.